LIBRARY SERVICES AND USER SATISFACTION FOR THE SANDWICH STUDENT: THE CASE OF UNIVERSITY OF CAPE COAST - Afful-Arthur, P (UDS International Journal of Development, 2016)
Sandwich education has made it possible for people with peculiar time constraints to attain education hitherto impossible through conventional means. The significant advantage of this module of education has led to many Universities and Colleges of Education in Ghana adopting this concept. Having heeded to this global trend of flexibility of university education, and with 6,010 students currently on admission, the University of Cape Coast is credited to be one of the few public universities in Ghana to run a successful sandwich programme over time. The compressed nature of the sandwich academic calendar implies that library services need to be fashioned out extraordinarily to meet the information needs of such students. It is in the spirit of gauging the propriety of library services rendered in support of the sandwich programme that the satisfaction of sandwich students was assessed in a survey. To this end, the study examined the perception of library users on the quality of academic library services and its impact on their academic work. This study employed the descriptive survey research design to engage 200 Sandwich students who patronize the library. Self-administered questionnaire containing 37 open and close-ended items based on SERVQUAL as a tool for quality service measurement was used to elicit information from respondents, and analyzed using SPSS version 2.0. It emerged that an overwhelming majority of the sandwich students knew about the library and its services from persons other than library staff, with still a majority using the library for reference or library searches. Respondents also considered print library resources to be very relevant but considered internet access not so adequate to access the few academic databases that the library subscribes to. It is quite refreshing to realize that nearly a ninth of respondents (89%) claimed library staff were welcoming and courteous and 81% indicated that there was willingness on the part of staff to readily help. Respondents were of the view that the Library should increase the opening hours, if not more, at least to the level of what the regular students enjoy, a suggestion the author concurs. Also, accessibility to resources outside of the Library should be improved while Web 2.0 tools should be employed in the delivery of library services. More importantly, an efficient orientation or user education programme should be run for sandwich students. Â Keywords: Â Â Â Â Â Library services, Sandwich education, Sandwich students, SERVQUAL, University of Cape Coast, User satisfaction